2015
DOI: 10.1155/2015/989560
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Protects from Type-I Peritoneal Membrane Failure Inhibiting the Angiogenesis, Lymphangiogenesis, and Endo-MT

Abstract: Preservation of peritoneal membrane (PM) is essential for long-term survival in peritoneal dialysis (PD). Continuous presence of PD fluids (PDF) in the peritoneal cavity generates chronic inflammation and promotes changes of the PM, such as fibrosis, angiogenesis, and lymphangiogenesis. Mesothelial-to-mesenchymal transition (MMT) and endothelial-to-mesenchymal transition (Endo-MT) seem to play a central role in this pathogenesis. We speculated that Rapamycin, a potent immunosuppressor, could be beneficial by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…The mTOR pathway is involved in various pathological mechanisms of lymphangiogenesis, lymphatic metastasis and several cancer developments, including colorectal cancer, gastric cancer, liver cancer, breast cancer and uterine cancer 15–17 . Sirolimus known as a mTOR inhibitor has an antiproliferative effect on lymphatic vessels, and is clinically used for a difficult‐to‐treat lymphatic anomalies 12,13,18–20 . Sirolimus binds the FK‐binding protein 12, resulting in a complex that prevents phosphorylation and activation of 4EBP1 and S6K1 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR pathway is involved in various pathological mechanisms of lymphangiogenesis, lymphatic metastasis and several cancer developments, including colorectal cancer, gastric cancer, liver cancer, breast cancer and uterine cancer 15–17 . Sirolimus known as a mTOR inhibitor has an antiproliferative effect on lymphatic vessels, and is clinically used for a difficult‐to‐treat lymphatic anomalies 12,13,18–20 . Sirolimus binds the FK‐binding protein 12, resulting in a complex that prevents phosphorylation and activation of 4EBP1 and S6K1 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are other cell populations in the peritoneum that may also undergo a mesenchymal transition and collaborate in fibrotic diseases and specifically in PD-related fibrosis, as inflammatory bone marrow-derived circulating cells (fibrocytes), that could represent a 34% of total FSP1 + fibroblasts, and endothelial cells from blood vessels (endo-MT) (approximately 5%) [27,[29][30][31][32][33]. Besides TGF-β, it has been shown that endothelin-1 (ET-1) may also participate in endo-MT [28].…”
Section: Fibrogenic Capacity Of Peritoneal Populationsmentioning
confidence: 99%
“…Nevertheless, it has to be taken into account that MMT is a physiologic process necessary for wound healing during PD. Another possibility is to act on the consequences of MMT or mesenchymal transition of other cells populations instead, such as the increased angiogenesis or lymphangiogenesis [33,47]. The therapeutic options tested until the date are exposed below in detail and summarized in Table 2.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppressors, such as rapamycin, reduced peritoneum thickness, EMT by MCs, and levels of VEGF, TGF-β, and TNF-α [Gonzalez-Mateo et al, 2015]. In a rat model of encapsulating peritoneal sclerosis, intraperitoneal transplantation of human umbilical mesenchymal stem cells prevented peritoneal inflammation and fibrosis, suggesting a novel approach for cell therapy to peritoneal disorders [Fan et al, 2016].…”
Section: Emt: Possible Source Of Myofibroblasts During Peritoneal Fibmentioning
confidence: 99%